G349(P) Spectrum of paediatric traumatic brain injury presenting to tertiary paediatric emergency departments. (12th March 2018) - Ryan, E; Okafor, I; Blackburn, C; Barrett, M; Bolger, T; Molloy, E
Abstract : Aims: To determine the burden and aetiology of traumatic brain injuries (TBIs) presenting to tertiary paediatric emergency departments (PEDs). To determine the number of TBIs that are symptomatic, requiring imaging, re-presenting and requiring admission. Methods: Retrospective analysis of presentations of children 0–16 y to the 3 Paediatric Emergency Departments (PEDs) in a large urban area for 24 months. Diagnoses of head injury, intracranial bleed, skull fracture and those re-attending with the same complaint within 28 days were included. Hospital Symphony Emergency Department Information System (EDIS) and radiology (NIMIS) information systems were interrogated. Demographics, mechanism of injury, CT ordering and discharge destination were recorded. Demographic Data was extracted from the 2016 national census. Results: Head injury was diagnosed in 13 336 of 2 24 860 (5.9%) presentations to PEDs over 24 months. Median (range)age of presentation was 5.3 (0–16) years. The age profile was: Infants, n=1705 (12.8%), preschool age, n=6424 (48.2%) primary school age, n=3673 (27.6%), adolescents 12–16 y, n=1970 (14.8%). In adolescents, males predominant (73%) but gender equal in other age-groups. The rate of presentation is 3.7% per year at preschool age. Number admitted, transferred or reviewed was n=1460 (10.8%) with a neuroimaging rate of 4.4%. The triage category was 4 in 6718 (50%) and the place of accident was known in n=5298 (39.5%). Accidents occurred at home n=3325 (62.7%). In those with known mechanisms (52%), falls were predominant; n=3315 (47.5%) particularly from a height (n=1925) including from beds (n=298). Rugby alone accounts for a small number, n=229 (3.26%), but n=190 (18.4%) of the adolescent group. Conclusion: Preschool children have the highest incidence of head injury and the majority of injuries follow a fall. Sport accounts for a significant number of injuries in older children. Standardised reporting would improve information on demographics and mechanisms and allow targeted interventions in each age-group.